PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA PEGAWAI PADA KANTOR BAPPEDA PROVINSI BALI - I Gusti Ngurah Putu Sueka Jatiawan; Putu Agus Eka Rismawan; Ary Wira Andika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
Abstract Employee performance plays an important role in determining the achievement of organizational goals. The better the employee's performance, the easier it is to achieve organizational goals. This study aims to examine and analyze the influence of organizational culture, organizational commitment, and organizational citizenship behavior on employee performance at the Bali Provincial BAPPEDA Office. This research was conducted at the Bali Provincial BAPPEDA Office with a population of 155 employees consisting of 73 civil servants and 82 non-civil servants. The sample in this study was 73 employees with the status of Civil Servants. The sampling technique used in this study was a non-probability sampling technique, namely the purposive sampling method. Data are collected through interviews, documentation, and questionnaires. The data analysis technique used in this research is multiple linear regression analysis, which is processed using SPSS version 25 software. Based on the analysis results, this study shows that organizational culture positively and significantly affects employee performance. Organizational commitment has a positive and significant effect on employee performance. Organizational citizenship behavior (OCB) positively and significantly affects employee performance. This means that the organizational culture, organizational commitment, and organizational citizenship behavior (OCB) are better, and the performance of employees at the Bali Provincial BAPPEDA Office will increase too. To optimize the achievement of employee performance at the Bali Provincial BAPPEDA Office, they should pay more attention to and improve employee performance through efforts to promote and develop better organizational culture, organizational commitment, and Organizational Citizenship Behavior (OCB).